REGIONAL DISPARITIES OF SOCIO-ECONOMIC DEVELOPMENT IN NORTH MACEDONIA - Iliev, Dejan (Macedonian Geographical Society, 2019)
The current paper analyses regional disparities in North Macedonia at NUTS 3 level. This paper aims to determine whether there is a trend of decreasing or increasing the socio-economic disparities between the regions in the period after 2014. The analysis uses different socio-economic indicators such as the unemployment rate, gross domestic product per capita, gross fixed capital formation, and the number of active business entities. The main methods used in the research are analysis, comparison, and synthesis. The findings show that there are no significant reductions in regional disparities between regions. The Skopje Region remains the most developed region. Additionally, the findings reveal that if the Skopje Region is excluded from the analysis, interregional inequalities in the other seven regions are not very pronounced. Inequalities in regional development necessitate the implementation of the regional policy and development measures that will be discussed in the concluding remarks.
Keywords: socio-economic disparities, region, regional development, regional policy